AO-WAD: a proposal for accessible design within web engineering approaches - Martín, Adriana Elba (2012)
Mature Web Engineering (WE) approaches provide good resources for developing Web 2.0 applications. The state-of-the-art shows that many of these approaches have evolved for providing support to different issues during the development process of these kind of applications, as business-to-business process modeling, context-awareness, RIAs and live-regions or quality factors for improving users’ experience. Focusing on Accessibility, having full support usually means being tightly coupled to host process and models, which prevents conveying this support to other WE approaches. In this paper we introduce our proposal, called Aspect-Oriented Web Accessibility Design (AO-WAD), and generalize its use within WE approaches to provide Accessibility support applying Aspect-Orientation techniques. We embed AO-WAD into OOHDM and UWE methods to propitiate an ease understanding through a motivating example.